The Central Asian Economies of Water-energy security: The Future Role of Hydro and Fuel-based Systems - Aktymbayeva, Aliya; Orazgaliyeva, Arailym; Omarova, Aizhan; Tulaganov, Anvar; Akhmetova, Aigul; Tyurina, Yuliya; Troyanskaya, Marija (International Journal of Energy Economics and Policy, 2020)
This article provides an overview of the energy potential of Central Asian economies and in particular, the power sector of Tajikistan, with a special emphasis on the potential usage of coal since water availability for hydropower in the region depends on seasons and is already affected by climate change. With these restrictions, coal arises as to the economic alternative and coal-fired plants are considered in the country as a tool for development and new coal-fired plants are under construction and development of new coalmines is also proposed. The objective of this article is to achieve profitable capital investment in a 250 MW coal-fired thermal power plant situated in east part of Tajikistan. In this context, the article applies a mathematical model to estimate the quantitative advantages of coal alternatives. The cost analysis of the plant was carried out on the basis of total capital investment, operating cost (i.e. coal feedstock, maintenance and labour, and cost of pumping power) and revenue. Furthermore, the article discusses the main concerns of the government of Tajikistan in sustaining its economic development, and finally, describes the future role that hydro-coal power will play in this development. Keywords: energy security, energy economics, Central Asia JEL Classifications: 0130, Q400, Q430 DOI: https://doi.org/10.32479/ijeep.10267